Pengaruh Budaya Sekolah dan Kepemimpinan Kepala Sekolah terhadap Kinerja Guru Sekolah Dasar Negeri - nursita, ika; Murniati, Ngurah Ayu Nyoman; Sudana, I Made (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The background of this research is related to the performance of state elementary school teachers in Brebes District in planning, implementation and evaluation which has not been optimal. The main problems with school culture include the lack of awareness and responsibility in carrying out the official duties entrusted to them. The leadership of school principals in several schools is not yet optimal, whether as educators, managers, administrators, supervisors, leaders, innovators or as motivators. Based on the explanation above, research was carried out to analyze the influence of work discipline and the role of school principals on the performance of State Elementary School Teachers in Brebes District, Semarang City. This research aims to examine and analyze: (1) the influence of school culture on elementary school teacher performance, (2) the influence of school principal leadership on elementary school teacher performance, (3) the simultaneous influence of school culture and school principal leadership on elementary school teacher performance. This research method is quantitative descriptive. The research population was 540 people, the sample was 269 people. The instrument test used is the validity and reliability test. The classical assumption test uses the normality test, linearity test, multicollinearity test, and homogeneity test. Data analysis used simple linear regression test, multiple linear regression test, F test (ANOVA) and t test. Based on the research results, it can be concluded as follows: (1) School culture has a positive and significant effect on the performance of elementary school teachers in Brebes District, Brebes Regency. It is proven that t count is 55.806 > t table 1.97. The magnitude of the influence is 92.1%; (2) Principal leadership has a positive and significant effect on the performance of elementary school teachers in Brebes District, Brebes Regency, proven by t count 66.247 > t table 1.97. The magnitude of the influence is 94,3%; (3) School Culture and Principal Leadership simultaneously have a positive and significant influence on the performance of elementary school teachers in Brebes District, Brebes Regency, as proven by the Fcount value of 2612.378 > F table 3.02 with a significance level of 0.000 < 0.05. Simultaneous influence of 95 .2%. The suggestions put forward by researchers are: (1) Principals need to pay attention to the main things, that as a leader must have the ability to influence, mobilize, empower independence and autonomy, as well as develop the role of the Principal, policies and procedures for work spirit, (2 ) Teachers need to develop a school culture at work. Every teacher who commits violations should be willing to accept whatever sanctions are given to him. This cannot be separated from the leadership of the school principal to set an example. If he commits a violation, he is also ready to accept the sanctions given to him Key words: school culture, principal leadership, teacher performance